Financing Government Expenditures Optimally - Pinar Ayse Yesin (Swiss National Bank, Study Center Gerzensee, 2006)
In a simple cash-credit model, I study the effects of the combination of costly tax collection and tax evasion on fiscal and monetary policy for optimal resource allocation. Allowing the informal sector to use cash more intensively than the formal sector, I compute the optimal interest and tax rates for eleven OECD countries to finance their exogeneously given government spending. A comparison of the actual and optimal interest rates reveals that tax collection costs and tax evasion together can partly explain the cross-country differences in monetary policy, also rationalizing deviations from the Friedman Rule in the long-run.
Keywords: E63; H21; H26; 330; Optimal Interest Rates; Tax Collection Costs; Tax Evasion; Friedman Rule; Cashintensive Informal Sector; Inflationary Finance; Steuervermeidung; Besteuerungsverfahren; Geldpolitik; Geldmengensteuerung; Optimale Besteuerung; OECD-Staaten